(untitled) (Revista Ciência Agronômica, 2017)
The rapid and uniform establishment of rice crops is important for improving production. However, this condition is influenced by several factors, including the soil temperature when planting, which may delay seed germination and compromise the final stand. The aim of this study was to evaluate the behaviour of substances which have the effect of growth regulator when applied to the seeds of different rice cultivars under low-temperature conditions. The experiment was carried out in a completely randomised design with four replications in a bi-factorial scheme, where factor A was represented by the different products (gibberellic acid - AG3 , tiamethoxam - TMX, Haf Plus® - HAF, and a control with water - TEST), and factor B by the irrigated rice cultivars (IRGA 424, IRGA 425, Puitá INTA CL, and Avaxi CL). In addition, the experiment was repeated at temperatures of 17 °C and 25 °C in order to simulate low-temperature conditions. The results showed that AG3 is effective in increasing seed vigour in the rice cultivars at both temperatures, with the AG3 , TMX and HAF responsible for increasing germination percentage only at the temperature of 17 °C. The effect of the products is more pronounced at low temperatures, and is dependent on the cultivar; in cultivars which are sensitive to cold there is no effect from the products used.